Irinotecan Activates p53 With Its Active Metabolite, Resulting in Human Hepatocellular Carcinoma Apoptosis - Yuko Takeba; Toshio Kumai; Naoki Matsumoto; Sachiko Nakaya; Yoshimitsu Tsuzuki; Yohei Yanagida; Shinichi Kobayashi (Elsevier, 2007)
The topoisomerase I inhibitor irinotecan is widely used in anticancer therapy, although the detailed mechanism is still unclear. We investigated the apoptotic mechanisms of irinotecan in human hepatocellular carcinoma (HCC) cell lines (Huh7). SN-38 caused a significant decrease in cell proliferation and induced apoptosis in Huh7 cells and HepG2 cells. SN-38 significantly increased the expression of p53 protein and its phosphorylation at Ser15 in the nucleus and apoptosis-inducing proteins Bax, caspase-9, and caspase-3, while it significantly decreased the antiapoptosis protein Bcl-xL of Huh7 cells. SN-38-induced apoptosis was recovered after p53 antisense oligodeoxynucleotide (AS ODN) pretreatment, while Huh7 cells were precultured with p53 AS ODN, followed by the addition of SN-38 for 24 h. Furthermore, increases in p53 DNA-binding activity were observed in the nuclei of Huh7 cells after SN-38 treatment as shown by electrophoretic mobility shift analysis. SN-38 binding motifs were detected in the proximal promoter of p53 (bases −433 to −317 and −814 to −711). These results suggest that the p53-mediated apoptosis pathway is important in the anticancer effects of irinotecan in hepatocellular carcinoma. Keywords:: irinotecan, SN-38, Huh7 cell, apoptosis, p53 gene